2015
DOI: 10.1007/s00396-015-3685-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of ionic surfactant solution surface and effects of counter-ion therein—a joint investigation by simulation and experiment

Abstract: The main goal of the current paper is to investigate the surface structure of ionic surfactant solutions at molecular level and the influences of the counter-ion in this course. The used methods are molecular dynamics simulation and neutral impact collision ion scattering spectroscopy. The surfactants are sodium dodecyl sulfate and cesium dodecyl sulfate. With Material Studio (MS), the concentration-depth profiles of all the components in the surface layer have been simulated. With those profiles, the surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…28,30 However, this model is still limited because it artificially divides surfactant ions into two layers, which contradicts the continuous change of concentration determined by experimental techniques. 4,31 Also, this model focuses on surface excess only and does not address the surface potential issue explicitly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,30 However, this model is still limited because it artificially divides surfactant ions into two layers, which contradicts the continuous change of concentration determined by experimental techniques. 4,31 Also, this model focuses on surface excess only and does not address the surface potential issue explicitly.…”
Section: Introductionmentioning
confidence: 99%
“…A similar idea of surfactant immersion was proposed by Ivanov et al The immersion of ionic surfactants was found to enhance the efficiency of surfactant adsorption, and the two-layer model successfully explained the reason for the unexpected decreases of sodium dodecyl sulfate (SDS) adsorption at the oil–water interface. Potentially, this model may be used to explain several strange phenomena of soluble surfactants at the free interface and thin films. , However, this model is still limited because it artificially divides surfactant ions into two layers, which contradicts the continuous change of concentration determined by experimental techniques. , Also, this model focuses on surface excess only and does not address the surface potential issue explicitly.…”
Section: Introductionmentioning
confidence: 99%
“…All simulation processes were calculated by using the Materials Studio software package [19] . Firstly, the Visualizer module was used to build the oil phase, water phase and surfactant molecular models.…”
Section: Model Constructionmentioning
confidence: 99%
“…Soluble surfactants, especially ionic surfactants such as SDS, form thick adsorption layers at the air–water interface which cannot be sufficiently represented by infinitely thin layers assumed by adsorption models. The existence of a thick adsorption layer was proven by many experimental and simulation results such as NR, , X-ray reflectivity, neutral impact collision ion scattering spectroscopy (NICISS), SFG, ,, and MD. Because the adsorption layer is a few nanometers thick, there could be a surfactant-depleting region or under-monolayer adsorption underneath the first adsorption layer. , Although those changes in surfactant concentration cannot be detected by measurement techniques because of their limited probing depth, they still contribute to the surface tension drop . While the surface excess derived from the surface tension represents the whole system, the surface excess determined from RT and NR may come from only the first adsorption layer, so their values should be different.…”
Section: Problems Of Classical Theories In Comparison With Experimentsmentioning
confidence: 99%